Perancangan Perancangan Purbalingga Art Center dengan Pendekatan Arsitektur Kontemporer - Yohana Nursruwening; Aprianto, Kukuh; Basuki (Institut Teknologi Nasional Yogyakarta, 2024)
Purbalingga Art Center is an institution that holds a collection of art from a region and manages and organizes art activities, such as art exhibitions, art festivals, and others. Therefore, an option is needed that can handle the problem so that art exhibition activities in Purbalingga Regency can be carried out continuously, namely providing a suitable art exhibition space and housing with various facilities that support artists and tourists in being creative. Data collection methods from first parties or original sources directly and from other sources or articles. This data can be in the form of documentation or a complete description of the data needed for this research. The application of Contemporary Architecture in the design of the Purbalingga Art Center applies elements of comfort to every space and utilizes technology that is continuously developing with a style that depicts freedom.